Peran Pemerintah Dalam Mendorong Pendidikan Islam yang Inklusif Di Madrasah - Habibah, Ummu; Wahyudin, Wawan; Muhajir, Muhajir (Universitas Yudharta Pasuruan, 2023)
This research discusses the role of the government in promoting inclusive Islamic education in madrasah because it has a strategic role in shaping a noble and broad-minded generation. As a policy maker, the government is responsible for creating an educational environment that accepts differences and involves people from all walks of life, regardless of social, economic or cultural differences. In addition, the government helps build collaboration between madrasahs, communities and other relevant parties. To ensure the sustainability of the programme, the government also focuses on encouraging communities to support inclusive Islamic education. In addition, the government is committed to guaranteeing the educational rights of all students, including students with diverse social backgrounds or with special needs. This article provides an overview of how the government is responsible for supporting inclusive Islamic education in madrasahs. This research can help improve Islamic education policies and practices at the local and national levels. The government should continue to work to create an inclusive educational environment where every student has an equal opportunity to develop their potential in Islamic education.